Monetary policy and local industry structure - Alexander Popov; Lea Steininger (European Central Bank (ECB), 2023)
We study how monetary policy affects local market competition in a union of countries experiencing different economic conditions: the euro area. We find that when monetary conditions tighten (loosen), from the point of view of an individual economy, market concentration increases (declines). This effect is more pronounced when interest rates have been low-for-long, and it is stronger in sectors that are relatively more sensitive to changes in financing conditions. The underlying mechanism is a decline (increase) in short-term debt and investment by smaller and medium-size firms, relative to large firms, following monetary policy tightening (easing).
Keywords: E2; G1; G12; 330; Eurozone; Monetary Union; Monetary Policy; Low Interest Rates; Competition